Estudo da fermentação alcoólica do hidrolisado da biomassa cacaueira para produção de etanol - Kiefer, Rayane Grizotti (2018)
Among the residues generated by the agroindustries, it is highlighted those composed of lignocellulosic materials that can be transformed into valuable products. In order to study ways of minimizing waste and reusing them for energy production from renewable sources, it was worked with cocoa agroindustry residues to produce bioethanol through alcoholic fermentation at different initial concentrations of cells and supplementation of glucose. For this reason, an alkaline hydrogen peroxide pretreatment step (7.355% v/v) was carried out in order to facilitate the conversion of the cellulose and hemicellulose into sugars, as well as to hydrolyze with dilute sulfuric acid (0.5% w/v). During the fermentation tests under agitation at 30 ºC, with S. cerevisiae, the cell growth kinetics and the ART concentration, also the ethanol concentration was observed in 24 and 48 hours of the process. The highest ethanol levels were the ones that presented the uppermost maximum specific speed of cell growth. The highest levels of ethanol were found in the trials that presented the highest maximum specific velocity values (about 0.145 to 0.167 h-1 ), which were started with cell concentration of 0.80 and 1.00 g/L, reaching ethanol content of 5,8 and 4,3 ºGL in 48 hours, respectively. These results indicate the feasibility of the use of hydrolysate from cocoa biomass for bioethanol production.